(untitled) (Al-Mansour Journal, 2022)
The research aims to formulate an applied vision on the relationship between the practices of managers and the requirements of contemporary organizations. A sample of the Ministry of Housing and Construction was selected in three companies and the research was conducted on a sample of (144) of its employees at various administrative levels (manager, engineer, administrative). A number of hypotheses have tested for correlation and influence between search variables. Criteria for verifying these hypotheses have adopted, including the questionnaire as a main tool for collecting data and information, consisting of (66) sections covering research aspects (managers’ practices, requirements of contemporary organizations) , And the personal observation of the researcher and using a set of statistical tools to analyze data and information using the program (SPSS vr23).The research reached a number of conclusions,( the most important of which are: the direction of the managers of the companies investigated towards the accounting practices more than the other practices, and the companies’ efforts to reach the requirements of the contemporary organizations, especially the employees and their requirements and other requirements). In the light of the conclusions, a set of recommendations was formulated (corporate emphasis on managers to enhance their positive role, encourage employees, adopt a staff recycling approach, and a broader role for managers’ practices in providing the pillars for requirements to contribute to the activities and practices of managers).